PENGARUH GOOD CORPORATE GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PERUSAHAAN: (Studi Pada Perumda BPR Majalengka Kabupaten Majalengka Jawa Barat) - Nita Hernita; Asep Qustolani (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Abstract: This study aims to determine the effect of Good Corporate Governance and Human Resource Competence, on Company Performance. The population of this research is the company employees of Perumda BPR Majalengka. The sample selection using random sampling technique, the sample obtained amounted to 58 employees 58 research data. The type of data used in this research is quantitative data. The data collection method used primary data in the form of questionnaires and verification by using a quantitative approach. The data analysis technique used in this study is multiple linear regression analysis, coefficient of determination, partial significance test and simultaneous test using SPSS version 24 software tools. company performance, and the hypothesis simultaneously shows that Good Corporate Govarnance and Human Resource Competence have an effect on company performance